Intermolecular Radical C(sp3)−H Amination under Iodine Catalysis. Issue 22 (18th April 2019) - Bosnidou, Alexandra E.; Muñiz, Kilian
Abstract: The direct amination of aliphatic C−H bonds has remained one of the most tantalizing transformations in organic chemistry. Herein, we report on a unique catalyst system, which enables the elusive intermolecular C(sp 3 )−H amination. This practical synthetic strategy provides access to aminated building blocks and fosters innovative multiple C−H amination within a new approach to aminated heterocycles. The synthetic utility is demonstrated by the synthesis of four relevant pharmaceuticals. Abstract : Radically new : A process for the intermolecular C−H amination of aliphatic positions is based on the combination of a catalytic amount of iodine, an iodine(III) oxidant, visible light, and sulfonamides. Under these conditions, amidyl radicals are generated that promote the selective functionalization of C−H bonds.